Protocol for an Exploratory RCT of the Traumatic Stress Relief Intervention With Persons With Lived Experience of Leprosy in Addis Ababa, Ethiopia - Safa Kemal Kaptan; Marekegn Habtamu; Solomon Getahun; Beletshachew Tadesse; Ayse Akan; Adeline Pupat; Cécile Bizouerne; Nusrat Husain (Journal of Tropical Medicine)
Trial Registration: The UK’s Clinical Study Registry: ISRCTN868254411